Research on Optimization Strategy to Data Clustered Storage of Consistent Hashing Algorithm - Ningjia Qiu; Xiaojuan Hu; Peng Wang; Huamin Yang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
This paper has been withdrawed due to has major technical problems.---------------------------------------------------------------------This paper presents a consistent hashing data optimize multiple copy distributed clustered storage placement strategy, using technology to create a virtual node and aliquots storage area to ensure the balanced distribution of data storage. With the speed of data processing accelerated, it is possible for clusters actual required to complete the expansion, and complete the development of adaptive optimization. Experiments show that the execution speed has effectively improved to ensure the load balance. With possible extensions and reducing problems treatment in actual situation, oscillation has little impact on the load balancing, and the execution time is consistent with the proportion of the load trends.